Hemostatic abnormalities in dogs with naturally occurring heatstroke. Issue 3 (8th March 2017) - Bruchim, Yaron; Kelmer, Efrat; Cohen, Adar; Codner, Carolina; Segev, Gilad; Aroch, Itamar
Abstract: Objective: To investigate hemostatic analyte abnormalities and their association with mortality in dogs with naturally occurring heatstroke. Design: Prospective observational study. Setting: University teaching hospital. Animals: Thirty client‐owned dogs with naturally occurring heatstroke. Interventions: None. Measurements and Main Results: Citrated and EDTA blood samples were collected at presentation and at 4, 12, 24, 36, and 48 hours postpresentation (PP). Hemostatic tests performed included platelet count, prothrombin and activated partial thromboplastin times (PT and aPTT, respectively), antithrombin activity (ATA), total protein C activity (tPCA), fibrinogen, and D‐dimer concentrations. The overall survival rate was 60% (18/30 dogs). Older age, higher heart rate and rectal temperature at presentation, and time from onset of clinical signs to presentation were significantly associated with mortality. Hemostatic analytes at presentation were not associated with mortality. Prolonged PT and aPTT at 12–24 hours PP, lower tPCA at 12 hours PP, and hypofibrinogenemia at 24 hours PP were significantly ( P < 0.05) associated with mortality. Increased D‐dimer concentration and low ATA were common at all time points, but were not associated with mortality. The frequency of disseminated intravascular coagulation (DIC) increased in nonsurvivors throughout hospitalization, but the development of DIC was not associated with mortality. The number of abnormal coagulation disturbances during the first 24 hours was significantly higher in nonsurvivors ( P = 0.04). Conclusions: Hemostatic derangements are common in dogs with naturally occurring heatstroke. Alterations in PT, aPTT, tPCA, and fibrinogen concentrations appear to be associated with the outcome at 12–24 hours PP, exemplifying the need for serial measurement of multiple laboratory hemostatic tests during hospitalization, even when within reference interval on presentation. The development of DIC, as defined in this cohort, was not associated with mortality; however, nonsurvivors had significantly more coagulation abnormalities during the first 24 hours PP.